A global perspective on inflation and propagation channels - Luca Gattini; Huw Pill; Ludger Schuknecht (European Central Bank (ECB), 2012)
This paper revisits the evidence on the monetary policy transmission channels. It extends the existing literature along three lines: i) it takes a global perspective with aggregate series based on a broader set of countries (ca 70% per cent of the global economy) and a longer time (1960-2010) than previous studies. It, thereby, internalises potential international transmission channels (i.e. via global commodity prices); ii) it examines the interaction between monetary variables, asset prices (notably residential property) and inflation; and iii) it looks at the role of public debt for consumer price developments. On the basis of a VAR analysis, the study finds that i) global money demand shocks affect global inflation and also global commodity prices, which in turn impact on inflation; ii) global asset/property price dynamics appear to respond to financing cost shocks, but not to shocks to global money demand. Moreover, positive house price shocks exert a significant influence on inflation. From a global perspective, the study suggests recognition of global externalities of commodities and asset values as well as the close monitoring of real estate price developments.
Keywords: E31; E51; E62; C32; F42; 330; global house prices; global inflation; global money; VAR